2008
DOI: 10.1345/aph.1k666
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones in Type 2 Diabetes: A Cardiology Perspective

Abstract: Although the glycemic efficacy of TZDs is comparable to that of metformin, adverse effects and higher costs make TZDs less appealing for initial therapy. Among the TZDs, pioglitazone should be considered based on cardiovascular safety data. In combination with metformin, pioglitazone may be particularly beneficial for patients with diabetes and metabolic syndrome. For patients on rosiglitazone who are achieving glycemic goals and tolerating the therapy without apparent complications, rosiglitazone may be conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 60 publications
0
21
0
2
Order By: Relevance
“…However, large-scale clinical studies also have suggested that TZDs increase risks of heart failure (HF) in patients with T2D (Robinson, 2008;Zinn et al, 2008). Furthermore, clinical studies and meta-analyses of rosiglitazone (RGZ) clinical trials failed to establish clear cardiovascular benefits and in fact raised concerns that RGZ may increase cardiovascular events risk, especially cardiac death (Robinson 2008), although this matter is still subject to controversy (Lago et al, 2007;Nissen and Wolski, 2007;Khanderia et al, 2008). In addition, it has been well documented that treatment with TZDs (e.g., RGZ) is associated with fluid retention, edema, and exacerbation of heart failure, probably due to renal mechanism (Staels, 2005;Yang and Soodvilai, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, large-scale clinical studies also have suggested that TZDs increase risks of heart failure (HF) in patients with T2D (Robinson, 2008;Zinn et al, 2008). Furthermore, clinical studies and meta-analyses of rosiglitazone (RGZ) clinical trials failed to establish clear cardiovascular benefits and in fact raised concerns that RGZ may increase cardiovascular events risk, especially cardiac death (Robinson 2008), although this matter is still subject to controversy (Lago et al, 2007;Nissen and Wolski, 2007;Khanderia et al, 2008). In addition, it has been well documented that treatment with TZDs (e.g., RGZ) is associated with fluid retention, edema, and exacerbation of heart failure, probably due to renal mechanism (Staels, 2005;Yang and Soodvilai, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While metformin has also been shown to prevent weight gain and improve blood glucose levels in hypertensive patients who received combination therapy of calcium antagonist (nitrendipine) and beta-blocker (atenolol) [94], in combination with drugs blocking the rennin-angiotensin system (ACEI or ARB), metformin may be associated with lactic acidosis and acute renal failure in patients with reduced renal function [95]. Whilst thiazolidinedione drugs (TZDs) may prove useful in the metabolic syndrome, or type 2 diabetes, a large concern has been expressed over the cardiovascular risks associated with rosiglitazone and pioglitazone [96]. Hsiao et al [97] performed retrospective cohort study of 473,483 newly diagnosed patients with type 2 diabetes in order to evaluate the associations between oral antihyperglycemics (TZDs including rosiglitazone and pioglitazone, sulfonylureas, and metformin) with myocardial infarction, congestive heart failure, angina pectoris, stroke and transient ischemic attack.…”
Section: Pharmacological Treatments For the Metabolic Syndrome As A Pmentioning
confidence: 99%
“…This effect is thought to be mediated via the PI3K signaling pathway in skeletal muscle (4,17,24). However, there have been discussions about the therapeutic effects of the currently available TZDs in the management of type 2 diabetes (21). The major concern of the TZD PPAR␥ agonists is that they have problems in fluid retention and weight gain and the increased risk of congestive heart failure (21,33,39).…”
mentioning
confidence: 99%
“…However, there have been discussions about the therapeutic effects of the currently available TZDs in the management of type 2 diabetes (21). The major concern of the TZD PPAR␥ agonists is that they have problems in fluid retention and weight gain and the increased risk of congestive heart failure (21,33,39). Additionally, TZD treatment has been shown to decrease bone mineral density in type 2 diabetic humans and animals (16,21,27,40).…”
mentioning
confidence: 99%
See 1 more Smart Citation